Two highly selective and sensitive fluorescent probes design and apply to specific detection of hypochlorite. (February 2019) - Chen, Li-Dong; Ding, Hong-Lin; Wang, Ning; An, Yue; Lü, Cheng-Wei
Abstract: In this paper, two simple probes (L1 andL2 ) have been designed and synthesized for detection of ClO − with large Stokes shifts (about 200 nm). Both probes can react with ClO − in less than one min and display obvious changes in fluorescence, which showing potential ability of detection ClO − in real time. ES-MS analysis was utilized to confirm our design strategy and the possible detection mechanism. Owing to the delicate difference of structure of two probes, L2 has a significant fluorescence ratio response to ClO − and the fluorescence ofL1 is quenched.L1 has a longer emission wavelength, better response characteristics and weaker cytotoxicity (IC50 28.1 μM) as compared withL2 . The detection limit ofL1 is even as low as 0.09 μM. What's more, it is successfully used in monitoring ClO − real water samples and in living cells. Graphical abstract: Highlights: Two fluorescent sensors with 1, 3, 4-thiadiazole and 2-(2'-hydroxyphenyl) benzoxazole moiety was designed to detect hypochlorite. DFT calculations were used to assist designing these sensors. ES-MS analysis was used to confirm our design strategy and the detection mechanism. Both sensors had large Stokes shifts and shown very low detection limit, fast and highly selective fluorescence response to ClO − . The sensorL1 could successfully apply for the determination of ClO − in real water samples and in living cells.